Programming in K–12 Science Classrooms. - Sengupta, Pratim; Dickes, Amanda; Voss Farris, Amy; Karan, Ashlyn; Martin, David; Wright, Mason (Communications of the ACM, 2015)
The article looks at how how introducing K-12 students to visual computer programming can led to greater interest and success in text-based programming. Details are provided on teachers using the agent-based visual programming language and modeling platform ViMAP in the classroom. Information is also provided on how teachers integrated programming into curricula.